Experimental evaluation of the role of inorganic phosphorus for terrestrial carbon degradation in stream hyporheic zones. (16th August 2022) - Attermeyer, Katrin; Harjung, Astrid; Schelker, Jakob; Weigelhofer, Gabriele
Abstract: The hyporheic zone (HZ) is a hotspot of carbon processing in stream ecosystems as a consequence of the mixing of organic matter and nutrients from ground water and surface waters. However, major knowledge gaps exist regarding the drivers of microbial activity and carbon processing in the HZ among stream ecosystems with different carbon sources and sediment properties. We investigated the impact of algal dissolved organic matter (DOMalgal ) and inorganic phosphorus (P) on the degradation of soil DOM (DOMsoil ) by hyporheic microorganisms in two laboratory experiments. In our first experiment, we explored the influence of different ratios of DOMalgal to DOMsoil with and without P additions on microbial respiration and DOM composition in laboratory hyporheic microcosms under oxic conditions. Here, we used glass beads colonised by stream microorganisms resembling a pristine stream system. As the addition of DOMalgal increased P concentrations, we added P to adjust the P concentrations to the same level of the pure DOMalgal in a second batch. In our second experiment, we determined the aerobic microbial respiration of HZ‐sediments from 20 streams along a land‐use gradient in Austria incubated with DOMsoil . Again, we performed the experiments with and without P additions to see whether effects on microbial respiration depended on the ambient P concentrations of the streams. Aerobic microbial respiration in the hyporheic microcosms decreased with increasing DOMsoil proportions. When P concentrations were adjusted to the P level of the DOMalgal, aerobic microbial respiration rates were similar between the different DOM mixtures in the microcosms, mainly stimulating the degradation of humic‐like DOM fractions. This highlights the stimulating effects of the P additions on hyporheic microbial respiration and humic‐like DOM degradation in pristine streams. However, P additions caused a significant increase in microbial respiration in only one of 20 natural HZ‐sediments, suggesting that aerobic microbial respiration rates rarely were controlled by P availability in the investigated streams. We conclude that nutrient pulses can, but do not necessarily, stimulate microbial activity and terrestrial carbon degradation in the HZ of streams. Nevertheless, at low ambient nutrient concentrations (i.e., in pristine streams) terrestrial carbon degradation in the HZ can be accelerated when nutrient pulses occur, which has consequences for CO2 outgassing and the organic matter quality in the stream and its export to downstream sections.